Cortical activation in elderly patients with Alzheimer’s disease dementia during working memory tasks: a multichannel fNIRS study - Ruan, Nairong; Li, Xingxing; Xu, Ting; Zhao, Zheng; Mei, Xi; Zheng, Chengying (Frontiers in Aging Neuroscience, 2024)
Objective This study aimed to investigate cortical activation and functional connectivity in the cortex during working memory (WM) tasks in patients with Alzheimer’s disease (AD) using functional near-infrared spectroscopy (fNIRS). Methods A total of 17 older adults with AD and 17 cognitively normal (CN) participants were recruited. fNIRS was utilized to monitor oxygenated hemoglobin (HbO) concentrations in the frontotemporal lobe, while participants performed WM tasks to examine WM impairments in subjects with AD. Student’s t-test for continuous variables and the chi-square test for categorical variables were used to compare the clinical and HbO variables between the AD and CN groups. Functional connectivity was analyzed using Pearson’s correlation coefficient between the time series of each channel-to-channel pair. Results The changes in HbO concentrations and cortical activations during the WM task showed that the HbO concentration curve of the CN group was higher than that of the AD group during the encoding and maintenance phases of the WM task. Although in the brain region scale, there were no significant differences in average HbO concentrations between the two groups, many channels located in the frontal and temporal lobes showed significant differences (p < 0.05) in the average HbO (channels 7 and 32) and slope HbO values (channels 7, 8, 9, 23, 30, 34, and 38) during the WM task. The average functional connectivity of the AD group was significantly lower than that of the CN group (p < 0.05). The functional connectivity was stronger in the frontopolar (FP) region than in other areas in both groups. Conclusion This study revealed there were significant differences in HbO concentration in older adult patients with AD compared to CN during the WM task. The characteristics of HbO measured by the fNIRS technique can be valuable for distinguishing between AD and CN in older adults.